ANALISIS PENGELOLAAN KEUANGAN UMKM PADA SEKTOR PARIWISATA DI KOTA PONTIANAK (STUDI KASUS PELAKU UMKM DI TEPIAN SUNGAI KAPUAS PONTIANAK) - Aprianda, Dinda; Kristiawati, Endang; Afif, Ali (Jurnal Akuntansi, Auditing dan Investasi, 2022)
This study focuses on analysis of the financial management of Ministry of Micro, Small and MediumEnterprises (MSMEs) in the tourism sector in Kota Pontianak which aims to describe how MSMEs arefinancially managed and the government's efforts to regenerate MSME excecutant. This study usesinterviews with respondents, with a population and sample of four business excecutant on the banks ofthe Kapuas River, Pontianak. Data collection uses a structured interview method with the theme of theconcept of survival during a pandemic and financial reports. The analysis tool uses triangulation. Thedata analysis technique used is the data validity technique. Based on the results of the analysis of theconcept of survival during the pandemic and the financial statements obtained, it can be concluded thatthe financial management of MSMEs of the Kapuas River, Pontianak is quite good in terms ofinvestment, operations and strategy, but not good enough in controlling because MSME excecutant onlycontrol finances based on daily receipts without the recording process so that many MSME excecutantneed to record a minimum of profit and loss statements so that financial management is more optimal.The government in regrowing MSMEs is very good because it provides assistance ranging from DirectCash Assistance to People's Business Credit for MSME excecutant so that they can run their businesses.